2021
DOI: 10.1088/1755-1315/664/1/012053
|View full text |Cite
|
Sign up to set email alerts
|

Life Cycle Assessment (LCA) in the construction of healthcare buildings. Analysis of environmental impact

Abstract: Currently the optimization of raw materials, energetic efficiency and the reduction of environmental impact are aspects of such importance at the time of choosing a product, process or system. The healthcare buildings are a kind of building composed by a whole group of systems, products and processes. This means a great margin for improvement in energy efficiency and environmental impact caused during the construction as well. The main goal of this project is to verify the viability of applying a case of study… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 42 publications
0
2
0
Order By: Relevance
“…In order to obtain a comprehensive vision of the impacts, LCA also needs to be performed on medical packaging, including shipping containers, sharps containers, and drug trays [23]. When considering reusable packaging materials against their disposable alternatives, it is usually found that employing reusable medical packaging produces fewer greenhouse gas emissions, consumes less water, and creates less landfill waste.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…In order to obtain a comprehensive vision of the impacts, LCA also needs to be performed on medical packaging, including shipping containers, sharps containers, and drug trays [23]. When considering reusable packaging materials against their disposable alternatives, it is usually found that employing reusable medical packaging produces fewer greenhouse gas emissions, consumes less water, and creates less landfill waste.…”
Section: Literature Reviewmentioning
confidence: 99%
“…In order to understand the impacts of medical equipment and procedures also been done on the disposal and management of medical waste. More specifically, scientists have performed LCA analysis on the wastewater produced by the removal of pharmaceuticals and by hospital laundry, as well as solid waste treatment [23]. Ultimately, the study of the life cycle impacts of single-use vs. reusable medical devices needs to cover equipment manufacture and use, packaging, reprocessing methods, and waste disposal aspects.…”
Section: Literature Reviewmentioning
confidence: 99%